2017
DOI: 10.1088/1361-6560/aa9102
|View full text |Cite
|
Sign up to set email alerts
|

RBE and related modeling in carbon-ion therapy

Abstract: Carbon ion therapy is a promising evolving modality in radiotherapy to treat tumors that are radioresistant against photon treatments. As carbon ions are more effective in normal and tumor tissue, the relative biological effectiveness (RBE) has to be calculated by bio-mathematical models and has to be considered in the dose prescription. This review (i) introduces the concept of the RBE and its most important determinants, (ii) describes the physical and biological causes of the increased RBE for carbon ions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
156
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(168 citation statements)
references
References 217 publications
(300 reference statements)
4
156
0
Order By: Relevance
“…The RBE is a nonlinear function of the physical dose and it is estimated by means of dedicated radiobiological models of the interaction between the particle beam and the irradiated system. 23 In this study, we validate the WED-space method for the estimation of motion-induced variations in the physical dose, which is independent of radiobiological modeling. We also provide a comparison between physical and biologically effective (i.e., RBE-weighted) dose variations due to respiratory motion, thus evaluating the feasibility of physical dose metrics to quantify the impact of organ motion in our context.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…The RBE is a nonlinear function of the physical dose and it is estimated by means of dedicated radiobiological models of the interaction between the particle beam and the irradiated system. 23 In this study, we validate the WED-space method for the estimation of motion-induced variations in the physical dose, which is independent of radiobiological modeling. We also provide a comparison between physical and biologically effective (i.e., RBE-weighted) dose variations due to respiratory motion, thus evaluating the feasibility of physical dose metrics to quantify the impact of organ motion in our context.…”
Section: Introductionmentioning
confidence: 76%
“…Nevertheless, the impact of respiratory motion on biologically effective dose distributions related to physical dose variations was investigated and resulted in an overall lower sensitivity, thus suggesting the feasibility of physical dose metrics for the WED‐space method validation. The integration of a radiobiological model will permit to obtain the missing information. Despite these limitations, this study showed that the WED‐space method is able to provide simulations of the dosimetric effect of irregular breathing when imaging data are lacking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the multitude of the factors and mechanisms of action underlying tumor and normal tissue responses to radiation therapy, particle RBE also depends on many biological, patient‐ and treatment‐specific factors, including the particle type, incident beam energy, and number and types of treatment fields . Because particle RBE is a ratio of the doses of radiations that produce the same biological effect, it is important to note that the biology and treatment factors (e.g., total dose and fraction size) used as low LET reference radiation are as important to accurate determinations of clinical RBE as particle beam biology and treatment factors.…”
Section: Introductionmentioning
confidence: 99%
“…32 Because of the multitude of the factors and mechanisms of action underlying tumor and normal tissue responses to radiation therapy, particle RBE also depends on many biological, patient-and treatment-specific factors, including the particle type, incident beam energy, and number and types of treatment fields. [33][34][35][36][37][38][39] Because particle RBE is a ratio of the doses of radiations that produce the same biological effect, it is important to note that the biology and treatment factors (e.g., total dose and fraction size) used as low LET reference radiation are as important to accurate determinations of clinical RBE as particle beam biology and treatment factors. For all of these reasons, mathematical models of particle RBE are essential for efforts to translate the results of in vitro and in vivo experiments probing mechanisms of action to the clinical setting, thus facilitating the optimization and personalization of hadron therapy treatment planning.…”
Section: Introductionmentioning
confidence: 99%